ANALISIS PRIORITAS MASALAH KESEHATAN DI KABUPATEN SLEMAN YOGYAKARTA - Dwi Putri Sulistiya Ningsih; Sri Sahayati; Isa Dharmawidjaja (Jurnal Sains Kesehatan, 2018)
Health development is carried out through the implementation of improvements through: Health efforts, health financing, human resources, pharmaceuticals, medical devices, foods, health information management, and community empowerment. Priority analysis of health problems is the basic activity used to plan health programs. This study was intended to describe the priority of health problems in Sleman District, Indonesia. This study used descriptive design. Data collected through assessment from documentation and interviews. Interviews were conducted with health workers at the Sleman District Health Office. Health problems measured their rank using the Hanlon method. In this valuation method is based on four components, namely the magnitude of the problem, the seriousness of the problem, the estimated effectiveness of the solution, and PEARL (propriety, economy, acceptability, availability of resources, legality). The results of this study were found in five main health problems in Sleman, namely; (1) Measles, there was an outbreak even though measles immunization coverage  90% nationally and at least 80% at the district level (Score 37.5). (2) Maternal Mortality Rate (83.30 per 100,000 live births in 2014, 63.27 per 100,000 live births in 2013 (score 36). (3) DHF-related deaths were 4 people with IR of 50.6 per 100,000 population (score 24) (4) Morbidity of diarrhea in 2014 was 214 per 1000 inhabitants (score 22). (5) In 2014 new cases of smear + TB were 442 people, with a total number of cases (prevalence) 546 (score 20). The five main health problems in Sleman District were measles, maternal mortality, DHF, diarrhea, and tuberculosis. Measurements with the Hanlon Method are easy to do, and the costs incurred are relatively low, so they can be routinely carried out in Sleman District. Keywords: analysis, health, problem priority, Sleman